Manuscript of novel - Carr, Roger Vaughan, 1937- (1948)
Un-revised first MS of the novel, Dune Bush, writer for the Commonwealth Literary Fund Fellowship, 1965. 270 p.
Manuscript reference no. : NLA MS 1752.
Typescript original.
Mr. Carr is an Australian author who was rewarded a Commonwealth Literary Fund Fellowship.
Keywords: Carr, Roger Vaughan, -- 1937- -- Archives; Authors, Australian -- 20th century -- Archives; Authors